Social Media in Shoulder & Elbow Surgery: An Analysis of Twitter and Instagram - Ramkumar, Prem N.; Navarro, Sergio M.; Cornaghie, Margaret M.; Haeberle, Heather S.; Hameed, Hafsah; Schickendantz, Mark S.; Ricchetti, Eric T.; Iannotti, Joseph P. (International Journal of Sports Medicine, 2018)
Social media provide a unique method of analyzing outcomes and quality in medicine. The purpose of this observational study was to investigate the nature of social media content related to shoulder and elbow (S&E) surgery posted by patients, surgeons, and hospitals. A public search of Instagram for a two-year period yielded 1,177 patient-related posts. A categorical system assessed the perspective, timing, tone, and content of each post. Twitter accounts of 77 S&E specialists from the top five ranked U.S. News & World Report institutions were analyzed for activity and content. 5,246 Twitter and Instagram posts for the institutions were analyzed for frequency and content. Most patient-related posts were by patients (68%), postoperative (82%), positive (87%), and centered on return-to-play for Tommy John (34%), surgical site for shoulder arthroplasty (52%), and activities of daily living for rotator cuff repair (22%). 37% of surgeons had active accounts averaging 46 posts, 87% of which were practice advertisements. Hospitals averaged 273 posts over the 2-year period, focusing on education (38%) and community (18%). S&E patients share outcomes on social media in a positive tone with procedure-dependent emphases. Surgeons on social media use sites for practice augmentation. Hospitals often focused posts towards educating the community.
Keywords: social media; Instagram; Twitter; shoulder; elbow; shoulder arthroplasty